IMPROVING SPEAKING ABILITY USING AUDIOVISUAL MEDIA IN CLASS XI TKI 2 SMK NEGERI 5 SURABAYA - Brams Dwiyansyah Abdul Jalal Ibrahim Noor; Rini Damayanti; Sumara Arisanthi (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Speaking ability is one of the most important language skills, especially in the context of vocational education such as vocational schools. This ability not only supports students in communicating effectively in the school environment, but also prepares them to enter the world of work. At SMK Negeri 5 Surabaya, especially class team, as well as interacting with clients. In class XI TKI 2 SMK Negeri 5 Surabaya, it is hoped that the use of audiovisual media can be an effective strategy to overcome these problems. By presenting relevant and interesting material through videos, short films, or multimedia presentations, students can be more involved in the learning process and motivated to improve their speaking skills. This media integration can also create a more dynamic and interactive learning environment, so that students can practice speaking more confidently. The weaknesses found by students were lack of self-confidence, limited vocabulary, and lack of ability to express ideas in a structured manner. The conditions of the learning environment using conventional learning methods do not involve students actively in the speaking process. Keywords: Speaking, Skills, Audio visual, Learning, Media, Students